PENGEMBANGAN APLIKASI ANDROID BERUPA WORKBOOK FISIKA BERBASIS MOODLE SEBAGAI PENDUKUNG MOBILE LEARNING UNTUK SISWA SMA - Veni Apriani; Wisnu Broto (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2017)
AbstractThis research is to develop physics workbook with Android OS based Moodle an alternative learning for students. In addition to knowing the quality of mobile learning moodle-based media, according to the experts the material and Senior High School physics teacher and student response towards mobile learning that have been developed. This research to enhance the interest of students, the development of this application can also provide convenience for the students in understanding the concept through the workbook that can direct the students find the concept itself. The learning material is restricted to special theory of relativity for class XII Senior high school. In this Research, the method used is research and development. Based on small scale field trials retrieved response students strongly agree (SS) with a percentage of 83.67%, while the large scale field trials 91.08% of the score is ideal. And based on the average score results validation expert material of 87.50%, results validation 84.25% of media experts, the results of the empirical test of 78.49% physics teacher, and student test results of 79.23%, thus it can be concluded that Physics workbook developed already qualify as media supporting learning, mobile learning for senior high school students. Learning media mobile learning using softwaremoodle can be accessed online through mobile learning media.Keywords: Android, Workbook, Mobile Learning, Theory of Special Relativity, Moodle.